Pengaruh Collective Bargaining Agreement dan Perceived Organizational Support terhadap Kinerja Karyawan yang dimoderasi Komitmen Organisasi di PT Internusa Caterindo selama Masa Pandemi Covid-19 - Lukiyana Lukiyana; Muhammad Yusuf (Universitas Bunda Mulia, 2022)
This study aims to determine the effect of Collective Bargaining Agreement (CBA) and Perceived Organizational Support (POS) on Employee Performance during the Covid-19 pandemic moderated by Organizational Commitment at PT Internusa Caterindo. The population in this study were employees of PT Internusa Caterindo in the Delta Silicon area of Cikarang. The research sample was 100 employees of PT Internusa Caterindo. The type of data created is primary data using a questionnaire that is filled in directly by one hundred respondents and then processes the data using Partial Least Square (PLS). Statistical results from research data show that the collective bargaining agreement has a positive and insignificant effect, perceived organizational support can have a positive and significant effect, organizational commitment has a positive and significant effect, the moderating effect of organizational commitment has not been able to strengthen the influence of the collective bargaining agreement and perceived organizational support on employee performance.